The meaning of life and health – a comparative study of the concepts of Aaron Antonovsky and Viktor Frankl - Sipowicz, Kasper; Podlecka, Marlena; Pietras, Tadeusz (Kwartalnik Naukowy Fides et Ratio, 2022)
The presented paper analyses the interdependencies between the meaning of life and health. The noo-psychotheoretical concepts derived from the logotherapeutic trend of Victor Frankl (1984, 2009, 2018) and the phenomenon of health in salutogenetic orientation by Aaron Antonovsky (1979, 1992, 2005) have been compared. As a result, the importance of a sense of meaning in the process of achieving health and the essence of the sense of meaning as one of the elements of health have been outlined.